Plasma proteomic analysis reveals altered protein abundances in HIV/HBV co-infection individuals with HCC and with liver cirrhosis - Yongxi Zhang; Ping Xu; Xingxia Yu; Ke Zhuang; Xien Gui; Rongrong Yang (Scientific Reports)
Abstract To develop a risk prediction model for hepatocellular carcinoma (HCC) by screening differentially expressed proteins (DEPs) in HIV/HBV coinfected patients with HCC and liver cirrhosis using proteomic techniques. DEPs were identified in plasma from HIV/HBV co-infected patients with HCC and liver cirrhosis using quantitative liquid chromatography-mass spectrometry (LC-MS). Mapping discovered proteins to the Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Disease Ontology (DO) databases yielded annotation information for DEPs. Differential plasma apolipoprotein A-1(APOA1) and transthyretin (TTR) expression levels were validated in 88 HIV/HBV co-infected individuals with HCC and liver cirrhosis. In total, 150 DEPs were discovered. The GO entries were primarily enriched for cutaneous immunological response mediated by circulating immunoglobulin and complement activation, as well as lipoprotein particle. The KEGG pathway enrichment was dominated by complement and coagulation cascades. Six of the 15 items enriched in the DO entries were related to lipid metabolism. APOA1, TTR, Prothrombin (F2), Antithrombin-III (SERPINC1), Alpha-2-HS-glycoprotein (AHSG), Alpha-2-macroglobulin (A2M) and Haptoglobin-related protein (HPR) were finally identified as hub proteins. Finally, a visual logistic model using immunoglobulin heavy variable 3–13 (IGHV3-13) and A2M to predict HCC were constructed. Significant variations in plasma APOA1 and TTR levels were found in HIV/HBV co-infected patients with HCC and liver cirrhosis. The screened hub proteins from DEPs can be employed as possible markers for early HCC detection. The developed HCC prediction model can be used to assess the risk of HCC in HIV/HBV co-infected cirrhotic individuals.